Audit Experience, Independence, and Professional Skepticism Against Fraud Detection: Time Pressure as a Moderating Factor - Kemala Maulida; Nurlita Novianti (Asia Pacific Fraud Journal, 2023)
The extraordinary effect of the Covid-19 outbreak, which pushes society and government to deal with a new normal in the face of situation uncertainty, raises the risk of fraud. The goal of this study is to predict and explain the effect of audit expertise, independence, and professional skepticism on fraud detection, with time pressure acting as a moderating variable. This inquiry employed the explanatory approach. The population comprises of BPK RI (The Audit Board of the Republic of Indonesia) and BPKP (Finance and Development Supervisory Agency) auditors from South Kalimantan Province, and the samples include 85 respondents. Surveys are used to collect data. The data suggest that audit knowledge and professional skepticism have a positive influence on fraud detection; independence has no effect on fraud detection; and time constraint has no effect on fraud detection.